SUPPLY MANAGEMENT, OPERATIONS AND MARKETING STRATEGIES FOR MSME SUSTAINABILITY: SYSTEMATIC LITERATURE REVIEW - Sudjatmoko, Agung; Halid, Andi Mohammad Nurdin; Saputro, Thomy Eko; Suprapto, Adi Teguh (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This research aims to present a systematic literature review addressing the development of supply management, operations, and marketing strategies which can sustain the success of the sustainability implementation for MSMEs. Several papers is collected from the scholarly journals published in the last five years. The findings indicate that digital entrepreneurship assistance, which can help develop digital skills and create more sustainable business flows, plays a significant role for MSMEs to sustain their business sustainability. A sustainable marketing strategy can help MSMEs increase market access, especially using digital strategies, making it easier for MSMEs to reach a wider market. Our systematic literature review has a limitation. The discovery of the sustainability practice on MSMEs only focuses on three aspects including supply management, operations, and marketing strategy. To complement the limitation of the current study, future research lies on the comparative analysis of sustainability practice on MSMEs and larger enterprises by considering other essential aspects including finance, human resources, and competitiveness. Operational management for MSMEs, especially MSMEs in the food sector, is also key in maintaining business operations during the COVID-19 pandemic. This study discuss, further using the Systematic Literature Review method to highlight Supply management, operations and marketing strategies for the sustainability of MSMEs so that they become a reference for business actors in developing their businesses and also for new business actors, of course, especially for policymakers in empowering and MSME development.